Liquid-liquid Slug Flow in a Microchannel Reactor and its Mass Transfer Properties - A Review - Rahul Antony; M. S. Giri Nandagopal; Nidhin Sreekumar; S. Rangabhashiyam; N. Selvaraju (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Mass transfer is a basic phenomenon behind many processes like reaction, absorption, extraction etc. Mass transfer plays a significant role in microfluidic systems where the chemical / biological process systems are shrinkened down to a micro scale. Micro reactor system, with its high compatibility and performance, gains a wide interest among the researchers in the recent years. Micro structured reac-tors holds advantages over the conventional types in chemical processes. The significance of micro re-actor not limited to its scalability but to energy efficiency, on-site / on-demand production, reliability, safety, highly controlled outputs, etc. Liquid-liquid two phase reaction in a microreactor system is highly demandable when both reactants are liquids or when air medium cannot be suitable. This arti-cle overviews various liquid-liquid flow regimes in a microchannel. Discussions on the hydrodynamics of flow in micro scale are made. Considering the importance of mass transfer in liquid-liquid systems and the advantage of slug regime over other regimes, the article focuses especially on the mass trans-fer between two liquid phases in slug flow and the details of experimental studies carried out in this area. The advantages of slug flow over other flow regimes in micro structured reactor applications are showcased. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)